Effects of combined estrogen and progestin administration on plasma lipoprotein metabolism in postmenopausal women. - B M Wolfe; M W Huff (The Journal of Clinical Investigation, 1989)
Treatment of postmenopausal women with low doses of estradiol-17 beta (1 mg/d) and dl-norgestrel (0.075 [corrected] mg/d) significantly reduced fasting serum levels of low density lipoprotein (LDL) cholesterol and lowered very low density lipoprotein (VLDL) triglycerides in four of five subjects. To explain these results, the kinetics of VLDL and LDL apolipoprotein (apo) B turnover were studied by injecting autologous 125I-labeled VLDL and 131I-labeled LDL into subjects before discontinuing long-term (4-yr) treatment with the estradiol-17 beta and dl-norgestrel and again 7 wk after stopping treatment. The 24% mean decrease in VLDL apo B pool size during treatment was associated with a significant increase in VLDL apo B fractional catabolic rate (15 +/- 1 vs. 11 +/- 1 pools/d), whereas production rate was similar to control (24 +/- 3 vs. 21 +/- 2 mg/kg per d). There was a significant 25% mean decrease in LDL apo B pool size (27 +/- 2 vs. 36 +/- 3 mg/kg) due to a significant decrease in total (8.3 +/- 0.3 vs. 11 +/- 1 mg/kg per d) and independent (3.3 +/- 0.5 vs. 6.6 +/- 0.8 mg/kg per d, P less than 0.05) LDL apo B production. Estradiol-17 beta together with dl-norgestrel lowered plasma VLDL by enhancing their clearance and LDL by reducing their production.